Mass media exposure and its impact on malaria prevention behaviour among adult women in sub-Saharan Africa: results from malaria indicator surveys - Yaya, Sanni (Glob Health Res Policy, 2018)
BACKGROUND: Mass media exposure plays a pivotal role in health communication and adoption of a healthy lifestyle. In this study, we aimed to measure the prevalence of malaria prevention behaviour among adult women in eight malaria-endemic countries in sub-Saharan Africa (SSA), and assess the influence of mass media exposure in the adoption of those behaviours. METHODS: For this study, we collected cross-sectional data on 46,822 women aged between 15 and 49 years from the Malaria Indicator Surveys (MIS) conducted in Burkina Faso, Ghana, Mali, Malawi, Kenya, Nigeria, Sierra Leone and Uganda. As the outcome variable, malaria prevention behaviour was proxied by the use of insecticide treated nets (ITNs) and uptake of antimalarial drugs in last pregnancy. RESULTS: The overall prevalence of sleeping under ITN and that of taking antimalarial drug during the last pregnancy was respectively 67.9% (95%CI = 66.6–69.2) and 72.8% (95%CI = 71.3–74.2). However, there were disparities in the prevalence of using ITN and antimalarial drug use across the study countries. In the multivariable regression analysis, not receiving malaria related information from radio, poster/billboards, community events, and health workers were found to be significantly associated with reduction in the odds of using ITN the previous night. For the use of antimalarial drugs during last pregnancy, the odds were 23% [OR = 0.773, 95%CI = 0.625–0.956] lower for those who did not receive malaria information on radio compared with those who received. CONCLUSIONS: These findings indicate a potentially important role of malaria information received through mass media on utilisation of ITN among women in SSA. More research is needed to explore the factors that limit the accessibility to malaria information through mass media.